2017
DOI: 10.1038/srep42303
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional insights into the catalytic mechanism of the Type II NADH:quinone oxidoreductase family

Abstract: Type II NADH:quinone oxidoreductases (NDH-2s) are membrane proteins involved in respiratory chains. These proteins contribute indirectly to the establishment of the transmembrane difference of electrochemical potential by catalyzing the reduction of quinone by oxidation of NAD(P)H. NDH-2s are widespread enzymes being present in the three domains of life. In this work, we explored the catalytic mechanism of NDH-2 by investigating the common elements of all NDH-2s, based on the rationale that conservation of suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…According to the proposed catalytic mechanism of Marreiros et al [22] , upon binding of NADH, FAD is reduced through hydride transfer to the N5 of the FAD isoalloxazine ring. The second proton needed for the full protonation of the reduced FAD is suggested to be provided by rearrangement of the hydrogen bond network around N1 in which a strictly conserved D302 is present.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the proposed catalytic mechanism of Marreiros et al [22] , upon binding of NADH, FAD is reduced through hydride transfer to the N5 of the FAD isoalloxazine ring. The second proton needed for the full protonation of the reduced FAD is suggested to be provided by rearrangement of the hydrogen bond network around N1 in which a strictly conserved D302 is present.…”
Section: Resultsmentioning
confidence: 99%
“…Marreiros et al [22] , recently proposed the first catalytic mechanism for NDH-2 family. In this study, which contemplates CTC formation coincidentally with NADH binding, aspartate 302 (D302), present in the vicinity of FAD, was observed to be totally conserved (100%), even among other members of the tDBDF superfamily.…”
Section: Introductionmentioning
confidence: 99%
“…The primary structure of NDH-2 commonly includes two GXGXXG motifs within the b-sheet-a-helix-b-sheet domains (Rossman fold), one for binding NAD(P)H and another for FAD or FMN (Wierenga et al, 1986). Although the crystal structures of NDH-2 from Saccharomyces cerevisiae (Ndi1; Feng et al, 2012) and the bacterial type NDH-2 from Caldalkalibacillus thermarum (Heikal et al, 2014) as well as from Staphylococcus aureus (Sena et al, 2015) have been solved, the actual mechanism of NADH:quinone oxidoreduction still remains unclear despite recently presented models (Marreiros et al, 2017). It is generally agreed that, in organisms where NADH oxidation is carried out solely by NDH-2s, the main function of these enzymes is to perform the respiratory chainlinked NADH turnover and the following donation of electrons to the protein complexes that produce the H + gradient powering ATP production (for review, see Melo et al, 2004).…”
mentioning
confidence: 99%
“…The aromatic character at W63 has been reported to be highly conserved among NDH-2s (Fig. 5 ) and suggested to stabilize the prosthetic group FAD in the enzyme 32 . The present study therefore identified a new role in substrate binding for these residues.…”
Section: Discussionmentioning
confidence: 95%